2023
DOI: 10.1002/cbdv.202300646
|View full text |Cite
|
Sign up to set email alerts
|

Combined Metabolite Analysis and Network Pharmacology to Elucidate the Mechanisms of Therapeutic Effect of Melastoma dodecandrum Ellagitannins on Abnormal Uterine Bleeding

Abstract: The abnormal uterine bleeding (AUB) is complex and usually leads to severe anemia. Melastomadodecandrum (MD) is clinically used for the treatment of metrorrhagia bleeding. The MD ellagitannins (MD‐ETs) had been evidenced being effective at hemorrhage, and exerts biological activities upon their metabolites including ellagic acid and urolithins. In this study, the blood‐permeated metabolites from theMD‐ETs were analyzed using LC‐MS approach, and 19 metabolites including ellagic acid and urolithin A derivatives … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 42 publications
1
0
0
Order By: Relevance
“…We previously demonstrated that TNF-α-induced EGFR activation is important for modulating the TME of GBM [40]. Recently, a network pharmacology analysis suggested that urolithins may act on the EGFR and Akt signaling for anti-abnormal uterine bleeding effect [73]. The present study corroborated that urolithins reduce the TME and inhibit tumor progression in GBM cells by regulating Akt and EGFR signaling pathways (Figure 8).…”
Section: Discussionsupporting
confidence: 84%
“…We previously demonstrated that TNF-α-induced EGFR activation is important for modulating the TME of GBM [40]. Recently, a network pharmacology analysis suggested that urolithins may act on the EGFR and Akt signaling for anti-abnormal uterine bleeding effect [73]. The present study corroborated that urolithins reduce the TME and inhibit tumor progression in GBM cells by regulating Akt and EGFR signaling pathways (Figure 8).…”
Section: Discussionsupporting
confidence: 84%